Perlindungan Hukum Pada Pelayanan Kesehatan Tingkat Pertama Di Kabupaten Kotawaringin Timur - Syiblunnur, Muhammad, Prof. Dr. Absori, S.H., M. Hum, Dr. dr. Hari Wujoso, Sp.F.,M.M (2017)
Providing of facilities and infrastruktur are the onsibility of the government, in the East Kotawaringin Regency there are 17 subdistricts, and each subdistrict has a primary health center. Several primary health center in contryside and other remote are happened inequality of health workers, this condition will be an obstacle to national development. The health development that pursued government is impossible to be realized if there is a gap of facilities and human recources in the health sector. The aim of this study is to describe the health care and the law protection on health care in the primary health center. The type this study is a qualitative with normative-empirical approach. The result of the study indicates that the effort in the primary health center in the East Kotawaringin Regency has not implemented. There are variety of obstacles that caused the minimum achievement, including the lack of human resources and facilities, and the geographical condition that complicate for health care effort. Individual health efforts that are invasive procedures in non-urban area primary health center are dominated by the nurse. Inequality of health care system between urban and non-urban area thus resulting legal and scientific pathology.